Revealing microstructural inhomogeneities with dark-field neutron imaging - Hilger, Almuth; Kardjilov, N.; Kandemir, T.; Manke, I.; Banhart, J.; Penumadu, D.; Manescu, A.; Strobl, Markus (Journal of applied physics, 2010)
Dark-field neutron tomography was applied to obtain three-dimensional volumetric data representing the distribution of micrometer and submicrometer sized structures in bulk samples. This is a size range that complements the range of direct spatial resolution. A phase grating setup implemented in a conventional imaging instrument enables corresponding tomographic investigations on reasonable time scales. Different samples were investigated and demonstrate the applicability of the method for the investigation of structural materials. Local variations in the small-angle scattering in BiSn, AlSi, and aluminum samples were mapped and the results are discussed with respect to the contrast formation of the method.
Gesehen am 15.05.2023